PJESMA NAD PJESMAMA U HRVATSKOGLAGOLJSKOM PARIŠKOM ZBORNIKU IZ 1375. GODINE. - STANKOVSKA, Petra (Slovo (05836255), 2025)
The paper focuses on the part of the text of the Song of Songs (1,1-11), which is attested in the Croatian Glagolitic Paris Miscellany written in 1375, kept in the French National Library in Paris under the signature Cod. slave 73 (CPar). The fragment from the Song of Songs under study is placed on ff. 178v-179v as a part of the office for the feast of the Nativity of the Virgin Mary, more precisely as a reading for the vigil of that feast. On the same place and in the same function, there is a reading from the Song of Songs in the Proprium sanctorum of the Croatian Glagolitic breviaries. After comparing the text in the Croatian Glagolitic breviaries of the 14th-16th centuries and in CPar, it is shown that the text in CPar is based on the same translation as the one in the breviaries, but has been significantly revised in terms of lexical corrections, bringing the text closer to the vernacular language in places that should not have been clear to an audience unfamiliar with Church Slavonic.